Impact of Different Grids on the Quality of Abdominal Radiography Images - Shekti, Shitoch Armandho Bimo; Sari, Ni Larasati Kartika; Hartoyo, Puji; Muliyati, Dewi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
Grids are additional accessory in radiography that absorb scatter radiation hoping to reduce blurriness on the image.  Various type of grids is available in the market so the effect of those on image quality needs to be evaluated. The purpose of this study is to compare the quality of abdominal radiography images using three variations of grids (moving and stationary grid) and without using a grid in order to see the best type or grids to produce the greatest image quality. Abdominal radiography exposure factors were used to expose two phantoms. Pro-Fluo 150 phantom was used as the object to measure image quality such as Signal to Noise Ratio (SNR), Contrast to Noise Ratio (CNR), and spatial resolution. A survey of five radiologists was also performed to evaluate the contrast and the visibility of objects’ boundaries in Anthropomorphic phantom images. The result of this study showed that the usage of various grids gave different values of SNR, CNR, and spatial resolution. The exposure factor of 70-75 kV in each mAs have the highest SNR value (52,64-78,31). Images obtained without a grid and exposure factor of 80-85 kV in each mAs have the highest SNR value (160,65-800,48). Images obtained from using moving grid also have the highest CNR and spatial resolution, with score of 3.72 – 7.62 and 3.7 lp/mm. The results of radiologists’ survey showed that the average score for moving grid’s images was 29.8 of 30 with a percentage of 99.33%. Therefore, it that can concluded that images obtained with moving grid have the best quality that can provides contrast and shows the boundaries between organs clearly in abdominal radiography. Based on this research, it’s recommended to use moving grid for abdominal radiography examinations.